Dinamika Peran Bahasa Indoesia di kalangan Gen-Z : Analisis Penggunaan Bahasa Gaul di Media Sosial - Jhon Roger Sitohang; Fonti Fai Banjarahor; Reni Wati Sagala; Moh. Surip (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This research aims to analyze the dynamics of the role of Indonesian language among Generation Z, with an emphasis on the use of slang language in the context of social media. Language as a means of communication holds crucial significance in social life, and its development reflects the changes in time and technology Generation Z, born between the mid-1990s and early 2010s, is a group that is highly exposed to digital media and actively engages in content creation. A descriptive qualitative method is employed to explore the impact of slang language usage on the practice of formal Indonesian language communication. The findings indicate that while slang supports the expression of identity and creativity, there is a risk of diminished understanding of formal Indonesian language. This research recommends the implementation of innovative educational campaigns and collaboration with influencers to raise awareness of the importance of proper Indonesian language usage. With the application of appropriate strategies, it is hoped that the Indonesian language can remain relevant and be effectively used by Generation Z, positioning them as agents of change in the preservation of language in the digital era.